Body, suffering and culture; an analysis of the concept of 'body techniques' for the study of the exchange between hurt-charity as social fact in total - Juan Pablo Matta (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
This article discusses different aspects linked to the ways in which suffering is given and compensated socially. At first it analyses the subject willing to place suffering within the framework of a broader exchange system that links sociologically action to pity (whereby the suffering is given) with the practice of charity. Secondly, it retrieves the “mausseano” concept of total social fact, which enlightens the multidimensional nature of the problem, clears the forms in which the individual and the collective are articulated in the specific obligations in which the exchange mobilizes. Finally, and from the perspective projected by the previous concepts, it explores the socio-cultural dimension of the suffering through the analytical category of "body techniques", using this concept to rebuild some of the social rationales underlying the phenomenon of suffering by proposing that it only findssense in the context of social relations in which it is expressed.